Corporate Governance and Loan-Syndicate Structure. (16th December 2021) - Bharath, Sreedhar T.; Dahiya, Sandeep; Hallak, Issam
Abstract: Firms with greater shareholder rights have a greater risk-shifting incentive, requiring more lender monitoring. Thus, a reduction in shareholder rights implies more diffused (less monitoring-intensive) loan syndicates. Using the passage of U.S. second-generation antitakeover laws as an exogenous shock that reduces shareholder rights as a natural experiment, we find that loan syndicates become significantly more diffuse after the passage of these laws. These results are confirmed in a large sample of bank loans made during the 1990–2007 period when the loan syndicate market matured. Our results show how corporate governance causally affects financial contracting and creditor control in firms.